2022
DOI: 10.1111/1462-2920.15920
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial chemoreceptor that mediates chemotaxis to two different plant hormones

Abstract: Summary Indole‐3‐acetic acid (IAA) is the main naturally occurring auxin and is produced by organisms of all kingdoms of life. In addition to the regulation of plant growth and development, IAA plays an important role in the interaction between plants and growth‐promoting and phytopathogenic bacteria by regulating bacterial gene expression and physiology. We show here that an IAA metabolizing plant‐associated Pseudomonas putida isolate exhibits chemotaxis to IAA that is independent of auxin metabolism. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 130 publications
(222 reference statements)
0
26
0
Order By: Relevance
“…The E. coli maltose-binding protein (MBP) is a primary model to study SBPs ( 48 , 49 ). We have used E. coli MBP and E6B08_RS28125, an amino acid-sensing SBP of P. putida ( 50 ), as models to study the pH robustness of ligand recognition in solute-binding proteins. Like the periplasmic LBDs, MBP and E6B08_RS28125 show extraordinary pH robustness and recognized their ligands, D-maltose and l -ornithine, respectively, over ranges of 8.5 and 8.0 pH units, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli maltose-binding protein (MBP) is a primary model to study SBPs ( 48 , 49 ). We have used E. coli MBP and E6B08_RS28125, an amino acid-sensing SBP of P. putida ( 50 ), as models to study the pH robustness of ligand recognition in solute-binding proteins. Like the periplasmic LBDs, MBP and E6B08_RS28125 show extraordinary pH robustness and recognized their ligands, D-maltose and l -ornithine, respectively, over ranges of 8.5 and 8.0 pH units, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Complementation of the PsPto‐ pscC mutant with pscC provided in trans resulted in a chemotaxis phenotype that was superior in its magnitude to the WT strain (Figure S3). Expression in trans from multicopy plasmids enhances cellular chemoreceptor levels and previous studies following a similar approach have also reported an increase in the magnitude of the chemotactic response (Fernández et al, 2016; Hida et al, 2020; Rico‐Jiménez et al, 2022).…”
Section: Resultsmentioning
confidence: 76%
“…IAA can be metabolized by rhizospheric bacteria (Donoso et al, 2017; Ebenau-Jehle et al, 2012; Lin et al, 2012; Scott et al, 2013), some of which like Pseudomonas putida show chemotaxis towards the auxin (Rico-Jiménez et al, 2022; Scott et al, 2013). Thus, IAA production by Chlamydomonas may attract and feed bacteria that could potentially be beneficially self-serving.…”
Section: Discussionmentioning
confidence: 99%